Cultural values and aesthetics in Chinese and Western oil painting: An investigation into their impact on artistic localization and integration influencing students’ outcomes - Xu, Xiaoyu; Xiao, Shimeng (Edelweiss Applied Science and Technology, 2025)
By examining how cultural values and aesthetics play into how Chinese and Western oil painting is incorporated with localization and integration, this study seeks to investigate the influence that both have. With this investigation is the meeting between traditional Chinese philosophies, more specifically Confucianism, Taoism, and Buddhism, and Western ideas based in realism, individualism, and perspective. Through a discussion of historical development, stylistic variation, and the general trend of artistic development currently, the study tries to show how cultural values affect artistic expression and education. In addition, the research looks at the influence of this artistic paradigm on students’ outcomes in art education. Its main focus is on the two Chinese and Western oil painting traditions, which contribute to creativity, technical proficiency, and cross-cultural artistic understanding. The study also examines how combining different creative approaches is advantageous in terms of stimulating creativity and increasing innovative viewpoints among students. The study makes use of case studies and surveys of art students to explore how cultural aesthetics affect the development of artistic skills and conceptual thinking by using qualitative and quantitative methods. Results indicated that an integration of Chinese and Western artistic principles in a balanced manner may lead to improved students’ adaptability and artistic vision to the point that it effectively supplements the current art education framework with a more global applicability. In the end, it shows the value of cultural understanding in artistic education and practice.